Reproductive Health Promotion Behavior of Infertility Women and Normal Women - Chaenam Lee; Naeyoung Lee (Korean Society of Women Health Nursing, 2019)
PURPOSE: To compare reproductive health promoting behaviors (RHPBs) of infertile women with those of normal women and identify effects of RHPB on infertility. METHODS: A total of 148 females (73 infertile women and 75 normal women) were enrolled in this study. Measurements included their general characteristics and RHPB using self-report questionnaires. Data were analyzed with descriptive statistics, χ2 test, ANCOVA, and hierarchical logistic regression using SPSS. RESULTS: There were significant difference in incomes, number of family, number of term deliveries, and number of abortions according to infertility diagnosis. Mean duration of infertility was 32.16 months. Only 12.32% women had known cause of infertility. The most common cause of infertility was unknown. Mean RHPB score was 3.98 for infertile women and 4.41 for normal women. In logistic regression, total RHPB (odds ratio [OR], 0.21) and safe sex of RHPB (OR, 0.66) were significant factors influencing infertility. Infertile women's total RHPB and subcategories of RHPB (safe sex behavior and sexual transmitted disease [STD] prevention) were lower than those of normal women. CONCLUSION: For infertility women, RHPB-related intervention programs are needed, especially information about safe sex behavior and STD prevention.